9 - University Crisis and Student Strikes in Africa: The Case of the University of Buea (Cameroon) - Piet Konings, (Journal of Higher Education in Africa, 2009)
The deepening crisis in African universities has had grave consequences for stu- dents who are faced with a dramatic deterioration in their living and study condi- tions and bleak prospects for future employment. The authoritarian management style and political control prevailing in most of these universities form formidable obstacles for students wishing to voice their grievances and organize in defence of their interests. However, African students seem not to be resigned to their fate and instead have displayed a growing activism that is reflected in various forms of protest, including strike actions. This study focuses on two recent violent strikes in the English-speaking University of Buea (UB) in Anglophone Cameroon. Like most other student protests in Africa during the ongoing process of economic and political liberalization, the UB students went on strike in an attempt to improve their unsatisfactory living and study conditions and to create democratic space within and outside the university. What was peculiar to the UB strikes was that they were inspired by deep feelings among the Anglophone student community of being more oppressed and marginalized than their Francophone counterparts, owing to their Anglophone identity, by the Francophone-dominated post-colonial state.